Preparation method of self-supporting polyaniline film
By spraying silicon nanoparticle ethanol solution on the polyaniline film, modifying particles are formed and embedded in the conductive network, the problems of cumbersome preparation process and unstable conductivity of film materials are solved, and self-supported polypropylene with high stability and high conductivity are achieved Aniline film.
Patent Information
- Application Number
- CN202411580738.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-21
AI Technical Summary
The film materials used in the absolute measurement of radioactive activity in the prior art are cumbersome in the preparation process, and the film is significantly increased after gold plating, and the conductive properties are unstable.
By spraying the ethanol solution of silicon nanoparticles onto the polyaniline film, the esterification reaction of the silicon nanoparticles and the para-aminobenzoic acid in the polyaniline film is made to form modified particles, which are closely embedded in the conductive network of polyaniline to isolate the acidity , the damage of alkaline solutions to the doping process.
The stability of the film's conductive properties is improved, the conductivity is significantly improved, and the decrease is less than 15% within 30 days, solving the problem of unstable conductivity.
Smart Images

Figure CN119490683A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nuclear technology, and in particular to a method for preparing a self-supporting polyaniline film. Background Art
[0002] In the process of measuring radioactive activity, the reliability of the measured activity value needs to be determined through the traceability method. As the basic method for determining radioactive activity, the absolute measurement method of radioactive activity is often used to establish national benchmark methods. It is the starting point of traceability. Its accuracy determines the level of radioactive activity measurement in the entire country. In the process of absolute measurement of radioactive activity, most radionuclides need to be made into thin film sources with high detection efficiency. The preparation of high-quality thin film materials is a key technology.
[0003] The membrane material used for absolute measurement of radioactive activity requires that the atomic number of the material be as small as possible, the membrane material be as thin and uniform as possible, have good electrical conductivity and remain stable for a long time.
[0004] For a long time, the main method used at home and abroad is to prepare the membrane material by dissolving polyvinyl chloride-vinyl acetate copolymer (VYNS) in 1,2-dichloroethane, and then make it conductive by gold plating or gold-palladium alloy plating. The process of this method is very cumbersome, and it often takes a week or even several weeks to complete a measurement. In addition, gold is a high atomic number element, and the absorption of the film increases significantly after gold plating.
[0005] With the great progress in the research of conductive thin film materials, it has become possible to use film materials with lower atomic numbers in the absolute measurement of radioactivity.
[0006] Polyaniline is a conductive molecule with a long-chain conjugated molecular structure formed by the polymerization of aniline molecules under certain dielectric conditions and oxidative environments. The doping of polyaniline is different from the doping mechanism of other conductive polymers that produce cationic vacancies under the action of oxidants. The number of electrons in polyaniline does not change during the doping process. Instead, H+ and anion pairs (such as Cl-, sulfate, phosphate, etc.) are generated by the decomposition of the doped proton acid and enter the main chain, combining with the N atoms in the amine and imine groups to form polarons and dipoles, which are delocalized into the π bonds of the entire molecular chain, so that polyaniline exhibits higher conductivity. The conductivity of undoped polyaniline is about 6.28×10-9S·m-1. After acid treatment, the conductivity of the intermediate polyaniline can be increased by about 10 orders of magnitude. Based on this unique doping mechanism, the doping and dedoping of polyaniline are completely reversible. The degree of doping is affected by factors such as pH and temperature, and shows corresponding changes in appearance and color. Therefore, polyaniline has electrochemical activity and electrochromic properties. However, this characteristic also makes the conductivity of the film unstable. Especially in the process of measuring radioactivity, the solution the film contacts is alkaline or acidic, which puts higher requirements on the stability of its conductivity. Summary of the invention
[0007] The embodiment of the present application provides a method for preparing a self-supporting polyaniline film, wherein an ethanol solution of silicon nanoparticles is sprayed on the polyaniline film, so that the hydroxyl groups on the surface of the silicon nanoparticles in the ethanol solution of the silicon nanoparticles and the carboxyl groups in the p-aminobenzoic acid in the polyaniline film undergo an esterification reaction to form modified particles, so that one end of the polyaniline long chain forms a stable chemical bond connection with the surface of the modified particles and is tightly embedded in the conductive network of the polyaniline. At the same time, the silicon nanoparticle covering layer can effectively isolate the acidic and alkaline solutions from damaging the polyaniline doping process, thereby improving the stability of the conductive performance of the film.
[0008] The present application provides a method for preparing a self-supporting polyaniline film, comprising:
[0009] preparing a silicon nanoparticle ethanol solution;
[0010] A polyaniline film is obtained by using a polyaniline / N-methyl-pyrrolidone solution, p-aminobenzoic acid and hydrochloric acid;
[0011] The silicon nanoparticle ethanol solution is sprayed on the polyaniline film to cause esterification reaction between the hydroxyl groups on the surface of the silicon nanoparticles in the silicon nanoparticle ethanol solution and the carboxyl groups in the p-aminobenzoic acid in the polyaniline film to form modified particles, thereby obtaining a self-supporting polyaniline film.
[0012] In some embodiments, the step of preparing the silicon nanoparticle ethanol solution comprises:
[0013] Grinding the single crystal silicon in anhydrous ethanol under a preset gas environment to obtain a first mixed liquid;
[0014] adding p-aminobenzoic acid and hydrochloric acid to the first mixed solution to obtain a second mixed solution;
[0015] After ultrasonically dispersing the second mixed liquid, the mixed liquid is filtered and allowed to stand to obtain a silicon nanoparticle ethanol solution.
[0016] In some embodiments, the preset gas includes argon, neon or helium.
[0017] In some embodiments, the ratio of the single crystal silicon to anhydrous ethanol is 100 ml of anhydrous ethanol added to every 20 g of single crystal silicon.
[0018] In some embodiments, after the second mixed solution is ultrasonically dispersed at 60° C. for 4 hours, it is filtered and allowed to stand.
[0019] In some embodiments, the step of obtaining a polyaniline film using a polyaniline / N-methyl-pyrrolidone solution, p-aminobenzoic acid and hydrochloric acid comprises:
[0020] performing oxygen plasma treatment on the spin-coated substrate to obtain a treated spin-coated substrate;
[0021] Dropping the polyaniline / N-methyl-pyrrolidone solution on the treated spin-coating substrate, and performing spin coating using a spin coater to obtain an undoped polyaniline film;
[0022] Drying the undoped polyaniline film and the spin-coated substrate together to remove N-methyl-pyrrolidone in the undoped polyaniline film;
[0023] The undoped polyaniline film with N-methyl-pyrrolidone removed and the spin-coating substrate are placed in water so that the undoped polyaniline film with N-methyl-pyrrolidone removed floats on the water surface, the water is changed at a preset time interval, the process is repeated for a preset number of times, and the film is fished out of the water to obtain the undoped polyaniline film with N-methyl-pyrrolidone removed without the spin-coating substrate;
[0024] Adding the undoped polyaniline film without spin-coating substrate and from which N-methyl-pyrrolidone has been removed into a mixed solution of p-aminobenzoic acid and hydrochloric acid for floating doping for a preset time to obtain a doped polyaniline film;
[0025] The doped polyaniline film is vacuum dried to obtain a polyaniline film.
[0026] In some embodiments, the preset interval time is 12 hours.
[0027] In some embodiments, the preset number of times is greater than 5 times.
[0028] In some embodiments, the preset time is 2 hours.
[0029] In some embodiments, the spraying time is 2 minutes.
[0030] The present application provides a method for preparing a self-supporting polyaniline film, wherein an ethanol solution of silicon nanoparticles is sprayed on the polyaniline film, so that the hydroxyl groups on the surface of the silicon nanoparticles in the ethanol solution of the silicon nanoparticles and the carboxyl groups in the p-aminobenzoic acid in the polyaniline film undergo an esterification reaction to form modified particles, so that one end of the polyaniline long chain forms a stable chemical bond connection with the surface of the modified particles and is tightly embedded in the conductive network of the polyaniline. At the same time, the silicon nanoparticle covering layer can effectively isolate the acidic and alkaline solutions from damaging the polyaniline doping process, thereby improving the stability of the conductive performance of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A flow chart of a method for preparing a self-supporting polyaniline film according to some embodiments is exemplified. DETAILED DESCRIPTION
[0032] In order to better understand the above technical solution, the technical solution of the present application is described in detail below through specific implementation methods.
[0033] In order to solve the above technical problems, the embodiment of the present application provides a method for preparing a self-supporting polyaniline film, wherein an ethanol solution of silicon nanoparticles is sprayed on the polyaniline film, so that the hydroxyl groups on the surface of the silicon nanoparticles in the ethanol solution of the silicon nanoparticles and the carboxyl groups in the p-aminobenzoic acid in the polyaniline film undergo an esterification reaction to form modified particles, so that one end of the polyaniline long chain forms a stable chemical bond connection with the surface of the modified particles and is tightly embedded in the conductive network of the polyaniline. At the same time, the silicon nanoparticle covering layer can effectively isolate the acidic and alkaline solutions from damaging the polyaniline doping process, thereby improving the stability of the conductive performance of the film.
[0034] Figure 1 The flowchart of a method for preparing a self-supporting polyaniline film according to some embodiments is exemplarily shown. The method includes S100-S300.
[0035] S100. Prepare a silicon nanoparticle ethanol solution.
[0036] In some embodiments, the step of preparing the silicon nanoparticle ethanol solution comprises:
[0037] The single crystal silicon is ground in anhydrous ethanol under a preset gas environment to obtain a first mixed liquid; in some embodiments, the preset gas includes argon, neon or helium. In some embodiments, the ratio of the single crystal silicon to anhydrous ethanol is 100 ml of anhydrous ethanol per 20 g of the single crystal silicon.
[0038] Specifically, 20 g of single crystal silicon can be placed in a grinding bottle, 99.99% pure argon, neon or helium is introduced, 100 g of grinding balls are added, and then 100 ml of anhydrous ethanol is added for grinding for 4 hours to obtain a first mixed solution. In some embodiments, the diameters of the grinding balls are 1, 2 and 3 mm, respectively, and the mass ratio is 2:3:5.
[0039] Add p-aminobenzoic acid and hydrochloric acid to the first mixed solution to obtain a second mixed solution.
[0040] Specifically, the first mixed solution can be taken out from the grinding bottle, and 10 ml of 1 mol / L p-aminobenzoic acid and a small amount of hydrochloric acid are added to the first mixed solution to obtain the second mixed solution.
[0041] After ultrasonically dispersing the second mixed liquid, the mixed liquid is filtered and allowed to stand to obtain a silicon nanoparticle ethanol solution.
[0042] In some embodiments, the second mixed solution is filtered and allowed to stand after being ultrasonically dispersed at 60° C. for 4 hours. In some embodiments, the second mixed solution is filtered using a 0.1 μm organic nylon filter membrane and allowed to stand for 24 hours.
[0043] S200, obtaining a polyaniline film using a polyaniline / N-methyl-pyrrolidone (NMP) solution, p-aminobenzoic acid and hydrochloric acid.
[0044] In some embodiments, the step of obtaining a polyaniline film using a polyaniline / N-methyl-pyrrolidone solution, p-aminobenzoic acid and hydrochloric acid comprises:
[0045] The spin-coated substrate is subjected to oxygen plasma treatment to obtain a treated spin-coated substrate.
[0046] Specifically, the spin-coated substrate is subjected to oxygen plasma treatment in an oxygen plasma treatment machine to obtain a treated spin-coated substrate. In some embodiments, the treated spin-coated substrate is detected to determine whether oxygen-containing functional groups exist on the surface of the spin-coated substrate. Specifically, an X-ray photoelectron spectrometer (XPS) can be used for determination. If present, proceed to the following steps.
[0047] The polyaniline / N-methyl-pyrrolidone solution is dropped onto the treated spin-coating substrate, and spin-coating is performed using a spin coater to obtain an undoped polyaniline film.
[0048] In some embodiments, the polyaniline / N-methyl-pyrrolidone solution is uniformly dropped on the treated spin-coating substrate, and the undoped polyaniline film is obtained by spin coating using a spin coater. In addition, if undoped polyaniline films of different thicknesses are required, the method used can be to adjust the rotation speed and the rotation time of the spin coater, so that dark blue undoped polyaniline films of different thicknesses can be obtained.
[0049] The undoped polyaniline film and the spin-coated substrate are dried together to remove N-methyl-pyrrolidone in the undoped polyaniline film.
[0050] Specifically, the undoped polyaniline film and the spin-coated substrate can be placed in a vacuum oven for drying, and the N-methyl-pyrrolidone solvent can be completely removed.
[0051] The undoped polyaniline film from which N-methyl-pyrrolidone has been removed and a spin-coated substrate are inserted into water so that the undoped polyaniline film from which N-methyl-pyrrolidone has been removed floats on the water surface, the water is changed at a preset time interval, the process is repeated a preset number of times, and the film is fished out of the water to obtain the undoped polyaniline film from which N-methyl-pyrrolidone has been removed without a spin-coated substrate.
[0052] Specifically, a three-dimensional translation stage can be used to control the undoped polyaniline film from which N-methyl-pyrrolidone has been removed and the spin-coated substrate to be inserted into water at a certain angle and insertion speed, so that the undoped polyaniline film from which N-methyl-pyrrolidone has been removed floats on the water surface.
[0053] In some embodiments, the preset interval is 12 hours. In some embodiments, the preset number of times is greater than 5 times.
[0054] The undoped polyaniline film without spin-coating substrate and from which N-methyl-pyrrolidone has been removed is added to a mixed solution of p-aminobenzoic acid and hydrochloric acid for floating doping for a preset time to obtain a doped polyaniline film. In some embodiments, the preset time is 2 hours.
[0055] The doped polyaniline film is vacuum dried to obtain a polyaniline film.
[0056] Specifically, before drying the doped polyaniline film, a three-dimensional displacement stage can be used to fix a copper ring supporting the film to scoop up the doped polyaniline film, and the pulling angle and pulling speed can be controlled to slowly pull the copper ring out of the page so that the doped polyaniline film is attached to the copper ring, and the polyaniline film can be obtained after vacuum drying.
[0057] S300, spraying the silicon nanoparticle ethanol solution onto the polyaniline film, so that hydroxyl groups on the surface of the silicon nanoparticles in the silicon nanoparticle ethanol solution and carboxyl groups in p-aminobenzoic acid in the polyaniline film undergo esterification reaction to form modified particles, thereby obtaining a self-supporting polyaniline film.
[0058] The S300 step is also referred to as the silicon nanoparticle in-situ coating step. Specifically, 10 ml of silicon nanoparticle ethanol solution can be taken, placed in a solution bottle of an electrostatic spraying device, and a transmission tube is opened. The polyaniline film is placed in a sample tray, and a collimator is set below the polyaniline film, with a size of 8-15 mm in diameter to control the coating range. The collimator can be made of materials with good electrical conductivity such as copper, aluminum and stainless steel. The electrostatic spraying voltage is set at 20 kV-30 kV, and the distance between the nozzle and the polyaniline film is 2-4 cm. In certain embodiments, the spraying time is 2 minutes.
[0059] Thus, in H + Under the catalytic action of , the carboxyl groups of p-aminobenzoic acid in the polyaniline film react with the hydroxyl groups on the surface of the silicon nanoparticle ethanol solution to form modified particles, so that one end of the polyaniline long chain forms a stable chemical bond with the surface of the modified particles and is tightly embedded in the conductive network of the polyaniline. At the same time, the silicon nanoparticle covering layer can effectively isolate the acidic and alkaline solutions from damaging the polyaniline doping process, thereby improving the stability of the film's conductive properties.
[0060] Example
[0061] Step 1: Preparation of Si nanoparticle ethanol solution
[0062] 20g of single crystal silicon is placed in a grinding bottle, 99.99% pure argon is introduced, and 100g of grinding balls (with diameters of φ3mm, φ2mm and φ1mm, respectively, in a ratio of 5:3:2) are added; 100ml of anhydrous ethanol is added, and the mixture is ground for 4 hours to obtain a first mixed solution; the first mixed solution is taken out, 10ml of 1mol / L p-aminobenzoic acid is added, and a small amount of hydrochloric acid is added; the solution is ultrasonically dispersed at 60°C for 4h; the solution is filtered through a 0.1μm organic nylon filter membrane, and allowed to stand for 24h to obtain an ethanol solution of silicon nanoparticles.
[0063] Step 2: Using polyaniline / N-methyl-pyrrolidone solution, p-aminobenzoic acid and hydrochloric acid to obtain a polyaniline film.
[0064] The polyaniline film is prepared by spin coating. First, the spin-coated substrate is treated with oxygen plasma in an oxygen plasma treatment machine, and an X-ray photoelectron spectrometer (XPS) is used to determine the presence of oxygen-containing functional groups on the substrate surface. The polyaniline / N-methyl-pyrrolidone solution is evenly dropped on the spin-coated substrate to obtain an undoped polyaniline film. The undoped polyaniline film and the spin-coated substrate are placed in a vacuum oven for drying, and the N-methyl-pyrrolidone solvent is completely removed to obtain an undoped polyaniline film without N-methyl-pyrrolidone. The undoped polyaniline film without N-methyl-pyrrolidone and the spin-coated substrate are inserted into water using a three-dimensional displacement stage to control a certain insertion angle and insertion speed, so that the undoped polyaniline film without N-methyl-pyrrolidone floats on the water surface. The undoped polyaniline film without N-methyl-pyrrolidone floats for 12 hours and the water is replaced once, and this is repeated for more than 5 times to obtain a substrate-free undoped polyaniline film. Add p-aminobenzoic acid and hydrochloric acid mixed solution respectively, float doping for 2 hours, and obtain an undoped polyaniline film without spin coating substrate and without N-methyl-pyrrolidone. Use a three-dimensional displacement stage to fix the film support copper ring to fish out the doped polyaniline film, control the pulling angle and pulling speed, slowly pull the copper ring out of the liquid surface, so that the doped polyaniline film is attached to the copper ring, and vacuum drying is performed to obtain the polyaniline film. The conductivity of the pretreated polyaniline film is greater than 20S / cm, and it can horizontally carry a mass greater than 50mg of material.
[0065] Step 3: spraying the silicon nanoparticle ethanol solution onto the polyaniline film.
[0066] Take 10ml of silicon nanoparticle ethanol solution, put it into the solution bottle of the electrostatic spraying device, and open the transmission tube. Place the polyaniline film on the sample tray, set a collimator under the film with a size of φ8mm-φ15mm to control the coating range. The collimator can be made of copper, aluminum, stainless steel and other materials with good conductive properties. The electrostatic spraying voltage is set at 20kV~30kV, the distance between the nozzle and the film is 2cm-4cm, and the spraying time is 2 minutes to obtain a self-supporting polyaniline film. Under the catalytic action of H+, the carboxyl group of p-aminobenzoic acid and the hydroxyl group on the surface of Si nanoparticles undergo esterification reaction to form modified particles, so that one end of the polyaniline long chain forms a stable chemical bond connection with the surface of the modified particles and is tightly embedded in the conductive network of polyaniline. At the same time, the silicon nanoparticle covering layer can effectively isolate the damage of acidic and alkaline solutions to the polyaniline doping process, and improve the stability of the conductive properties of the film. The conductivity of the self-supporting polyaniline film increased from 20 S / cm to 180 S / cm, and the conductivity decreased by less than 15% within 30 days.
[0067] In summary, the present invention provides a method for preparing a self-supporting polyaniline film, wherein an ethanol solution of silicon nanoparticles is sprayed on the polyaniline film, so that the hydroxyl groups on the surface of the silicon nanoparticles in the ethanol solution of the silicon nanoparticles and the carboxyl groups in the p-aminobenzoic acid in the polyaniline film undergo an esterification reaction to form modified particles, so that one end of the polyaniline long chain forms a stable chemical bond connection with the surface of the modified particles and is tightly embedded in the conductive network of the polyaniline, and at the same time, the silicon nanoparticle covering layer can effectively isolate the acidic and alkaline solutions from damaging the polyaniline doping process, thereby improving the stability of the conductive performance of the film.
[0068] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.
Claims
1. A method for preparing a self-supporting polyaniline film, characterized in that: include: preparing a silicon nanoparticle ethanol solution; A polyaniline film is obtained by using a polyaniline / N-methyl-pyrrolidone solution, p-aminobenzoic acid and hydrochloric acid; The silicon nanoparticle ethanol solution is sprayed on the polyaniline film to cause esterification reaction between the hydroxyl groups on the surface of the silicon nanoparticles in the silicon nanoparticle ethanol solution and the carboxyl groups in the p-aminobenzoic acid in the polyaniline film to form modified particles, thereby obtaining a self-supporting polyaniline film.
2. The method according to claim 1, characterized in that The steps of preparing the silicon nanoparticle ethanol solution include: Grinding the single crystal silicon in anhydrous ethanol under a preset gas environment to obtain a first mixed liquid; adding p-aminobenzoic acid and hydrochloric acid to the first mixed solution to obtain a second mixed solution; After ultrasonically dispersing the second mixed liquid, the mixed liquid is filtered and allowed to stand to obtain a silicon nanoparticle ethanol solution.
3. The method according to claim 2, characterized in that The preset gas includes argon, neon or helium.
4. The method according to claim 2, characterized in that: The ratio of the single crystal silicon to anhydrous ethanol is 100 ml of anhydrous ethanol added to every 20 g of single crystal silicon.
5. The method according to claim 2, characterized in that: After the second mixed solution was ultrasonically dispersed at 60° C. for 4 hours, it was filtered and allowed to stand.
6. The method according to claim 1, characterized in that The step of obtaining the polyaniline film by using a polyaniline / N-methyl-pyrrolidone solution, p-aminobenzoic acid and hydrochloric acid comprises: performing oxygen plasma treatment on the spin-coated substrate to obtain a treated spin-coated substrate; Dropping the polyaniline / N-methyl-pyrrolidone solution on the treated spin-coating substrate, and performing spin coating using a spin coater to obtain an undoped polyaniline film; Drying the undoped polyaniline film and the spin-coated substrate together to remove N-methyl-pyrrolidone in the undoped polyaniline film; The undoped polyaniline film with N-methyl-pyrrolidone removed and the spin-coating substrate are placed in water so that the undoped polyaniline film with N-methyl-pyrrolidone removed floats on the water surface, the water is changed at a preset time interval, the process is repeated for a preset number of times, and the film is fished out of the water to obtain the undoped polyaniline film with N-methyl-pyrrolidone removed without the spin-coating substrate; Adding the undoped polyaniline film without spin-coating substrate and from which N-methyl-pyrrolidone has been removed into a mixed solution of p-aminobenzoic acid and hydrochloric acid for floating doping for a preset time to obtain a doped polyaniline film; The doped polyaniline film is vacuum dried to obtain a polyaniline film.
7. The method according to claim 6, characterized in that The preset interval time is 12 hours.
8. The method according to claim 6, characterized in that The preset number of times is greater than 5 times.
9. The method according to claim 6, characterized in that The preset time is 2 hours.
10. The method according to claim 1, characterized in that The spraying time is 2 minutes.